Advantages of Using Learning Management System (LMS (in Teaching Writing Skill in Adult English Classes in Saudi Arabia - Albalawi, Nahed Hussain Khalaf (Journal of Educational and Psychological Sciences, 2022)
It is undeniable that technology has changed our ways of living. These changes are dramatically increasing in different parts of our life day by day. The pace of using technological advances in an academic setting is faster than others. For instance, In Saudi Arabia internet usage has attracted much attention in education. This matter is more noticeable for adult learners of the English language in the country. Among the four skills of writing, reading, listening and speaking. writing is considered as the most challenging skill for the Saudi English learners. Literature has numerous studies discussing different online programs and applications for different skills, including learning how to write in English in Saudi Arabia. However, the problem is that none of them focuses on Learning Management System, LMS, to improve adults’ writing skill in Saudi Arabia. Therefore, the purpose of this study is to investigate potential advantages of LMS on writing skills of adult English learners in Saudi Arabia. It can be predicted that in upcoming years, we, as teachers or educators, will be more skillful in writing since LMS is on the fast track to improve these skills.
Keywords: Learning management system; writing skill; English language; adult education; Saudi Arabia